Riset Eksperimen-Kuasi: Perlukah Mahasiswa Baru Program Studi Akuntansi dari Latar Belakang Sekolah Berbeda kuatir? - Sondakh, Antonius Grivaldi (Jurnal Pendidikan Akuntansi (JPAK), 2024)
Some of new students, especially from SMU-IPA, are worried that they will not be able to compete with their colleagues from SMU-IPS and SMK-Accounting. Using a quasi-experimental method, this research aims to answer these concerns by extending previous findings regarding the relationship between school background and understanding of basic accounting. The introductory learning of accounting in the first year is experimental manipulation. The subjects who became the experimental group were 3rd-semester students, while the subjects who became the control group were 1st-semester students. Using prospect theory, this research proves that although initially these concerns were justified, after receiving basic accounting studies, these concerns became unreasonable. Apart from answering the concerns of new students, the results of this research are useful for the accounting study program to convince prospective new students and their parents not to hesitate in choosing accounting as a study option for future careers.